Red-eyed tree frog - Cowley, Joy.; Bishop, Nic, 1955- (New York : Scholastic, 2006)
This frog found in the rain forest of Central America spends the night searching for food while also being careful not to become dinner for some other animal.
Notable/Best Books (A.L.A.)
School Library Journal
Wilson's Children
1.8
K-3
K-3
Keywords: Hylidae -- Central America -- Juvenile literature; Frogs; Tree frogs; Frogs; Tree frogs